Effect of chlorine atoms in choline chloride-monocarboxylic acid for the pretreatment of oil palm fronds and enzymatic hydrolysis. (January 2022) - Tnah, Shen Khang; Wu, Ta Yeong; Ting, Dennis Chiong Chung; Chow, Han Ket; Shak, Katrina Pui Yee; Subramonian, Wennie; Procentese, Alessandra; Cheng, Chin Kui; Teoh, Wen Hui; Md. Jahim, Jamaliah
Abstract: Choline chloride (ChCl) and various monocarboxylic acids (monochloroacetic acid, MCA; dichloroacetic acid, DCA; trichloroacetic acid, TCA) with increasing numbers of substituted chlorine atoms were utilized for the pretreatment of oil palm fronds (OPFs). To the best of our knowledge, this study was the first attempt to utilize these three novel solvents in biomass pretreatment. The result of ChCl:TCA was excluded due to instability in conducting the pretreatment. Under the recommended conditions of 120 °C and 60 min, similar delignification percentages of 75.96% and 74.89% were obtained for ChCl:MCA and ChCl:DCA, respectively. Enzymatic hydrolysis of the pretreated OPFs was demonstrated after pretreatment. By using ChCl:DCA, a shorter duration of enzymatic hydrolysis (24 h) enabled glucan conversion of pretreated OPFs up to 89%. Although a longer duration of 72 h was imposed, glucan conversion of only 82% could be obtained by using ChCl:MCA. Thus, a solvent with a higher number of chlorine atoms (ChCl:DCA) could lead to more effective enzymatic hydrolysis. The results were compared to the literature findings, and ChCl:DCA was determined to be one of the most effective solvents for biomass pretreatment under relatively mild conditions. Highlights: Application of solvents with increasing chlorine atoms in pretreatment of OPFs. Outstanding delignification performance was achieved by ChCl: MCA and ChCl: DCA. Enzymatic hydrolysis substantially enhanced by ChCl: DCA as compared to ChCl: MCA.